2014
DOI: 10.1134/s1021443714060193
|View full text |Cite
|
Sign up to set email alerts
|

Functional identification of ELO-like genes involved in very long chain fatty acid synthesis in Arabidopsis thaliana

Abstract: Very long chain fatty acids (VLCFAs) are essential lipid components in many plants. 3 Ketoacyl CoA synthase (KCS) catalyzes the condensation reaction to form 3 ketoacyl CoA in VLCFA synthesis. AtELO4 has been reported to be involved in VLCFA synthesis, functioning as a KCS in Arabidopsis. However, no stud ies on other three AtELO members have been reported. Here, we initially found by real time PCR in Arabi dopsis thaliana (L.) Heynh. that AtELO1, AtELO3, and AtELO4 displayed characteristic expression patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…3-Ketoacyl-CoA synthase (KCS) catalyses a condensation reaction to form 3-ketoacyl-CoA during very long-chain fatty acid synthesis 52 . A previous study showed that the phenotypic changes of kcs1-1 mutants included relatively thin stems and reduced resistance to low-humidity stress at a young age 56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3-Ketoacyl-CoA synthase (KCS) catalyses a condensation reaction to form 3-ketoacyl-CoA during very long-chain fatty acid synthesis 52 . A previous study showed that the phenotypic changes of kcs1-1 mutants included relatively thin stems and reduced resistance to low-humidity stress at a young age 56 .…”
Section: Discussionmentioning
confidence: 99%
“…They are widely distributed on the cell surface to prevent moisture and heat loss and are closely related to cell recognition specificity and tissue immunity. However, relatively little is known about long-chain fatty acid amides: most of the well-defined physiological functions, the metabolism underlying their biosynthesis, their degradation, and their cellular transport remain elusive [50][51][52] . In this study, we focused on the accumulation of essential enzymes related to the biosynthesis of lignin, flavonoids and fatty acids in tea plants in response to drought stress at the protein level.…”
Section: The Accumulation Of Proteins Related To Lignin Biosynthesis mentioning
confidence: 99%
“…In particular, two distinct enzymes catalyze the Claisen condensation reaction of the FAE cycle, the KCS-type enzymes that occur uniquely in plants, and the ELO-type enzymes that are phylogenetically more widely distributed 17 . Moreover, plant genomes contain a large number of ELO genes and even larger number of KCS genes 17 , 18 , 25 27 . Although this appears to be a characteristic widely dispersed among plant phyla, it is not as prevalent among the other components of the FAE system.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, two distinct enzymes catalyze the Claisen condensation reaction of the FAE cycle, the KCS-type enzymes that occur uniquely in plants, and the ELO-type enzymes that are phylogenetically more widely distributed 18 . Moreover, plant genomes contain a large number of ELO genes and even larger number of KCS genes 18,[32][33][34][35] . Although this appears to be a characteristic widely dispersed among plant phyla, it is not as prevalent among the other components of the FAE system.…”
Section: Discussionmentioning
confidence: 99%